Tom Clancy : [large type] target acquired - Bentley, Don; Clancy, Tom, 1947-2013 (Clancy, Tom, 1947-2013. Jack Ryan Jr. novel., 2021)
"Jack Ryan, Jr. would do anything for Ding Chavez. That's why Jack is currently sitting in an open-air market in Israel, helping a CIA team with a simple job. The man running the mission, Peter Beltz, is an old friend from Ding's Army days. Unfortunately, Ding had to cancel at the last minute and asked Jack to take his place. It's a cushy assignment--a trip to Israel in exchange for a couple hours of easy work--Jack could use the downtime. But when he hastens to help a woman and her young son, he finds himself the target of trained killers. Alone and outgunned, Jack will have to use all his skills to protect the life of the child"--Page 4 of cover.